1996
DOI: 10.1002/qj.49712252906
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of forecast errors to initial conditions

Abstract: The adjoint method has been used to calculate the sensitivity of short-range forecast errors to the initial conditions. The gradient of the energy of the day 2 forecast error with respect to the initial conditions can be interpreted as a sum of rapidly growing components of the analysis error. An analysis modified by subtracting an appropriately scaled vector, proportional to the gradient, provides initial conditions for a 'sensitivity integration' that can be used to diagnose the effect of initial-data errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(173 citation statements)
references
References 25 publications
9
163
0
1
Order By: Relevance
“…A short summary of the adjoint sensitivity technique is given here. For a more detailed introduction, see (Rabier et al, 1996). The forecast error can be quantified by means of the diagnostic function (or cost function)…”
Section: Adjoint Sensitivity Of Forecast Error To Initial Conditionsmentioning
confidence: 99%
“…A short summary of the adjoint sensitivity technique is given here. For a more detailed introduction, see (Rabier et al, 1996). The forecast error can be quantified by means of the diagnostic function (or cost function)…”
Section: Adjoint Sensitivity Of Forecast Error To Initial Conditionsmentioning
confidence: 99%
“…In the present study, the error in model forecast UTH follows similar pattern as observed in UTH derived from NCEP analysis. The impact of uncertainties in initial conditions on NWP model forecast is discussed by Rabier et al (1996). The effect of departure in NCEP analysis-derived UTH (Figure 3) are reflected in the subsequent WRF model forecast for all simulation periods ( Figure 6).…”
Section: Forecast Comparisonmentioning
confidence: 99%
“…Lorenz 1963;Rabier et al 1996) and model formulation (e.g. Buizza et al 1999), and this sensitivity depends on the actual flow (e.g.…”
Section: Introductionmentioning
confidence: 99%